Misoprostol (Cytotec) for Prevention of Ovarian Hyperstimulation Syndrome. A Preliminary Investigation. - Leonardo, Formigli; Rakotobe, Andriamaro Andriantsirombaka; Ramarolahy, Rija; Graziella, Badulli; Hanitra, Rasoarimanana; Nargis, Ashurova; Ramachandran, Krishnamoorthy (Journal of Fertility Biomarkers, 2019)
This preliminary study explores misoprostol as a preventive strategy for ovarian hyperstimulation syndrome. It outlines rationale, dosing considerations, and early safety signals, and calls for controlled trials to establish efficacy and risk–benefit.
Keywords: Ovarian Hyper Stimulation; Prevention; Luteolysis; Prostaglandins; Misoprostol.